2012
DOI: 10.4236/me.2012.31006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustainability of Current Account Deficits in Turkey

Abstract: Sustainability of the current account deficits in Turkey was evaluated according to the macroeconomic fundamentals together with discussing the composition of current account deficit and the way of financing to have insights about the future path of current account balance. Problem about current account deficits were considered as structural since they were caused by foreign trade deficits largely as an outcome of dependence of production and exports on imported intermediate goods. Furthermore, there were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Following the cointegration stability test, Hye and Siddiqui (2010) found that imports cause the exports from the period of 2003 and exports cause the imports from 1994 to 2004. Insel and Kayikci (2012) evaluated the current account deficit of Turkey and found that Turkey would continue to have current account deficits in the next years and sustainability of these deficits has become increasingly difficult. Kalyoncu and Ozturk (2010) found a unique long run or equilibrium relationship among real exports and imports in the case of Peru, while in the case of Colombia, Venezuela, Mexico, Brazil and Argentina, cointegration results indicated that these countries' current accounts are not sustainable in the long run.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Following the cointegration stability test, Hye and Siddiqui (2010) found that imports cause the exports from the period of 2003 and exports cause the imports from 1994 to 2004. Insel and Kayikci (2012) evaluated the current account deficit of Turkey and found that Turkey would continue to have current account deficits in the next years and sustainability of these deficits has become increasingly difficult. Kalyoncu and Ozturk (2010) found a unique long run or equilibrium relationship among real exports and imports in the case of Peru, while in the case of Colombia, Venezuela, Mexico, Brazil and Argentina, cointegration results indicated that these countries' current accounts are not sustainable in the long run.…”
Section: Literature Overviewmentioning
confidence: 99%
“…29 The crisis-growth-current account deficit-crisis circle still constitutes as an inherent fragility of the Turkish economy, despite the improvements in budgetary performance and a relatively tightly regulated banking and financial system. 30 The second and interrelated proximate challenge for the economy is centered on Turkey's overdependence on energy. In 2011, Turkey imported more than 90 per cent of its total liquid fuel consumption, comprising an energy import bill of approximately 55 billion US dollars.…”
Section: Turkey's Economic Challenges: Two Achilles Heelsmentioning
confidence: 99%
“…The Banking Regulation and Supervision Agency 1. See, for example, Sekmen (2008), Oguş and Sohrabji (2008), Akat and Yazgan (2013), İnsel and Kayıkçı (2012), Röhn (2012), Edgerly (2013), Kara (2013), Harvey and Gökoluk (2014), and Özata (2014), among others.…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, Sekmen (), Oğuş and Sohrabji (), Akat and Yazgan (), İnsel and Kayıkçı (), Röhn (), Edgerly (), Kara (), Harvey and Gökoluk (), and Özata (), among others.…”
mentioning
confidence: 99%